Тринадцать способов умереть: [повесть и рассказ] / Валерий Рощин - Рощин Валерий Георгиевич (Спецназ, 2006)
Экземпляры: ф.6 (20171214) / Инвентарный номер: 2224 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Р 81 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44